Notas explicativas : uma análise qualitativa doconteúdo apresentado por companhias de capitalaberto listadas na BM&FBOVESPA - Silva, Gabriela Dias da (2016)
This study analyzes the content that is being published by publicly traded companies listed on the BM&FBovespa in Explanatory Notes, considering the existing guidelines and the issues raised by the Technical Guidance OCPC 07 (2014) (voluminous material, reproduced normative content and irrelevant information). To achieve the objective, we have looking the information disclosed in Explanatory Notes of the companies belonging to the BM&FBovespa Special Segments in the years 2008, 2010, 2012 and 2014. The sample consists of 27 companies from the nine most representative segments, being considered only segments with more than three companies. This is an applied research, with the problem addressed in a qualitative way. It is descriptive about the objectives and the technical procedure is documentary. The data analysis was performed using content analysis. The results point out that for some categories there are no relevant differences in the content presented by the companies between the period pre and post convergence. Still, we understand that some information make hard the users understandability, when doubts arise whether the items were recognized or only disclosed. The increase of the material disclosed in Explanatory Notes was realized from 2010, which can be derived from the compulsory convergence to international standards by Brazilian companies. The irrelevant information and the reproduced content, normative or not, was noted from the same year. We have concluded that the presented content should be improved to contribute to the informative quality and to support users' decisions in order to extinguish from the Notes the observed irrelevant and immaterial aspects.